2020
DOI: 10.1016/j.surg.2019.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Should multifocality be an indication for completion thyroidectomy in papillary thyroid carcinoma?

Abstract: Background-Multifocality in papillary thyroid carcinoma (PTC) is common. The aim of this study is to determine whether patients with multifocal disease (MFD), treated with lobectomy alone, have an increased risk of contralateral lobe PTC, regional recurrence, and poorer survival.Methods-After institutional review board approval, PTC patients managed, from 1986 to 2015, with lobectomy alone were identified from an institutional database. PTC patients with pT3-T4 classification, nodal disease, or distant metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 25 publications
4
35
0
1
Order By: Relevance
“…One area of active debate includes the extent of thyroidectomy surgery between lobectomy and possibly CT and TT. 11,15 An important consideration in preoperative planning is risk of postoperative complications. In this national study, we sought to analyze rates of non–thyroid-specific postoperative complications in CT and TT with the goal of capturing uncommon complications that are evident with only a large multi-institutional cohort.…”
Section: Discussionmentioning
confidence: 99%
“…One area of active debate includes the extent of thyroidectomy surgery between lobectomy and possibly CT and TT. 11,15 An important consideration in preoperative planning is risk of postoperative complications. In this national study, we sought to analyze rates of non–thyroid-specific postoperative complications in CT and TT with the goal of capturing uncommon complications that are evident with only a large multi-institutional cohort.…”
Section: Discussionmentioning
confidence: 99%
“…As multifocality in PTC more commonly occurs incidentally as microscopic foci diagnosed on histology report, occult tumors may be missed when performing RFA. However, patients with unifocal and multifocal disease had similar outcomes [39]. Regardless of the fact that CNB was performed in all patients prior to RFA, it cannot eliminate aggressive variants of PTC.…”
Section: Discussionmentioning
confidence: 95%
“…Only 3% of total patients with multifocal PTCs underwent lobectomy, and only one patient developed recurrence in the contralateral lobe. However, Harries et al showed that unifocal PTC and multifocal PTC patients had similar rates of recurrence of the contralateral lobe, regional recurrence, and overall survival with a median follow-up of 58 months (16). RAI-T also did not decrease the risk of recurrence in PTC (17).…”
Section: Discussionmentioning
confidence: 99%